Smoking Behavior in Adolescents Using the Plan Behavior Theory Approach - Puspitosari, Dewi Retno; Urifah, Siti; Wahdi, Achmad; Maisaroh, Siti; Pratiwi, Tiara Fatma (International Journal of Psychosocial Rehabilitation, 2020)
Smoking is a behavior that is harmful to health, but there are still many people who do it, even people start smoking when he was a teenager. Factors influencing smoking behavior are knowledge factor, friend factor, parent factor, school environment factor, media factor, and attitude. The purpose of this study was to determine the factors that influence smoking behavior in adolescents. He research design used in this research is cross-sectional. The population of this study was all male students in SMK Global Menturo Sumobito Jombang totaling 321 male students. Sampling technique using a stratified random sampling method, this research sample obtained 72 respondents (class X), 56 respondents (class XI), and 50 respondents (class XII). The analysis technique used is the Chi-Square test and Spearmen Rho Test. The results showed that there were significant correlation which consisted of: knowledge factor (p = 0,022), friend factor (p = 0,039), school environment factor (p = 0,017), and parent factor (p = 0,003). There was no significant correlation between attitude (p = 0,490) and media (p = 0,174).